CHALLENGES AND SOLUTIONS FOR DEMOCRATIC STABILITY IN INDONESIA AFTER THE CANCELLATION OF ELECTION REGULATIONS - Hasudungan Hutagalung, Henokh; Sugianto; Sanusi, Anwar (Hukum Responsif, 2024)
This paper explores the impact of the cancellation of electoral regulations, specifically PKPU No. 9 of 2020, on the stability of democracy in Indonesia. The decision by the Indonesian Supreme Court (Mahkamah Agung RI) to annul this regulation has created significant legal uncertainty, potentially disrupting the simultaneous regional elections (Pilkada). This study aims to analyze the challenges faced by the government and the General Election Commission (KPU) in responding to this decision, and to evaluate solutions that can be implemented to maintain democratic stability. Utilizing a qualitative analysis method, the paper identifies key issues such as regulatory changes, the potential delay of Pilkada, and increased administrative burdens. The findings highlight the importance of legal certainty and effective coordination among the government, election authorities, and the public to address these challenges. The study also proposes several solutions to enhance the electoral process and uphold democratic integrity in the future.